Prevalence of Aflatoxin M1 in Milk of Bovine in and around Junagadh, Gujarat State of India - Hedpara, Jay R.; Sindhi, Samiulla H.; N., Sanjay; Kumar, Binod; Bhedi, Kirit R. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Aflatoxin M1 (AFM1) is a hydroxylated metabolite of aflatoxin B1 from a contaminated feed. Aflatoxins are toxic, mutagenic andcarcinogenic compounds produced as a secondary metabolite by the fungi Aspergillus flavus and A. parasiticus. The present study wasconducted to determine the prevalence of AFM1 in milk by using two different diagnostic methods, viz., Enzyme-Linked ImmunosorbentAssay (ELISA) and Lateral Flow Assay (LFA). A total of 200 milk samples were collected from the areas under Junagadh city and nearbyvillages. An overall 93.5% incidence rate of AFM1 contamination in milk samples was recorded. Out of 200 samples, 6 (3%) sampleswere found to contain AFM1 above the FSSAI standard limit (0.5 µg/L) and 145 (72.5%) samples had AFM1 above the standard limit asper EU legislation (0.05 µg/L). Out of total 200 samples, 50 representative samples ana
Keywords: : Aflatoxin M1 (AFM1; ELISA; Lateral Flow Assay; Milk